2007
DOI: 10.2139/ssrn.1026893
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Relationship Between Reviews and Sales: The Role of Reviewer Identity Disclosure in Electronic Markets

Abstract: C onsumer-generated product reviews have proliferated online, driven by the notion that consumers' decision to purchase or not purchase a product is based on the positive or negative information about that product they obtain from fellow consumers. Using research on information processing as a foundation, we suggest that in the context of an online community, reviewer disclosure of identity-descriptive information is used by consumers to supplement or replace product information when making purchase decisions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
152
2
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(168 citation statements)
references
References 72 publications
12
152
2
2
Order By: Relevance
“…First, we enrich the understanding of the influence of online reviews. At the market level, product sales are found to be influenced by the level of review ratings (Zhu & Zhang, 2010), the valence and volume of online reviews (Berger, Sorensen, & Rasmussen, 2010;Chevalier & Mayzlin, 2006;Duan et al, 2008), and the characteristics of review contributors (Forman, Ghose, & Wiesenfeld, 2008). However, this line of studies provides limited insight into individuals' cognitive processes with regard to how informational factors (e.g., factors related to information itself and information sources) may affect ones' decisionmaking process.…”
Section: Implications For Researchmentioning
confidence: 99%
“…First, we enrich the understanding of the influence of online reviews. At the market level, product sales are found to be influenced by the level of review ratings (Zhu & Zhang, 2010), the valence and volume of online reviews (Berger, Sorensen, & Rasmussen, 2010;Chevalier & Mayzlin, 2006;Duan et al, 2008), and the characteristics of review contributors (Forman, Ghose, & Wiesenfeld, 2008). However, this line of studies provides limited insight into individuals' cognitive processes with regard to how informational factors (e.g., factors related to information itself and information sources) may affect ones' decisionmaking process.…”
Section: Implications For Researchmentioning
confidence: 99%
“…Consequently, if the new Web vendors did not already have social or brand capital (Lowry et al, 2008), they had to find alternative ways to convince potential consumers of their trustworthiness. Such persuasion attempts have been, for example, through the use of privacy and security seals (Bélanger et al, 2002;Kim et al, 2008;Xu et al, 2010;Lowry et al, 2012) and high-quality and intuitive websites with attractive interfaces (McKnight et al, 2002;Gefen et al, 2003;Lowry et al, 2008) including logos , mobile websites and convincing consumer reviews (Forman et al, 2008).…”
Section: Trusting Beliefsmentioning
confidence: 99%
“…This pioneering work shows that insight into the composition of reviews is imperative in understanding the effects of reviews on consumer judgment, as consumers seem to react differently to different types of reviews. For example, by linking useful votes to the product rating of a review, several studies found that clearly negative or positive product ratings (i.e., 1-and 5-star ratings) are perceived as more useful than moderate ratings (i.e., 3-star ratings, see Danescu-Niculescu-Mizil, Kossinets, Kleinberg, & Lee, 2009;Forman, Ghose, & Wiesenfeld, 2008). Others found that the polarity of product ratings contribute to the perceived usefulness of reviews, such that negative reviews have more impact on consumer judgment than positive reviews (Basuroy, Chatterjee, & Ravid, 2003;Chevelier & Mayzlin, 2006;Sen & Lerman, 2007).…”
Section: The Content Characteristics and Perceived Usefulness Of Reviewsmentioning
confidence: 99%
“…We collected the useful votes and total votes given above posted reviews in the form: ''[number of useful votes] out of [number of members who voted] found the following review useful' (see Figure 1). By calculating the fraction of useful votes among the total votes, useful votes were translated into percentages ranging from 1 to 100 that indicate the 'perceived usefulness of a review' (Forman et al, 2008;Mudambi & Schuff, 2010).…”
Section: Perceived Usefulnessmentioning
confidence: 99%